Whole-genome de novo sequencing reveals unique genes that contributed to the adaptive evolution of the Mikado pheasant. Issue 5 (2nd May 2018) - Lee, Chien-Yueh; Hsieh, Ping-Han; Chiang, Li-Mei; Chattopadhyay, Amrita; Li, Kuan-Yi; Lee, Yi-Fang; Lu, Tzu-Pin; Lai, Liang-Chuan; Lin, En-Chung; Lee, Hsinyu; Ding, Shih-Torng; Tsai, Mong-Hsun; et al.
Abstract: Background: The Mikado pheasant ( Syrmaticus mikado ) is a nearly endangered species indigenous to high-altitude regions of Taiwan. This pheasant provides an opportunity to investigate evolutionary processes following geographic isolation. Currently, the genetic background and adaptive evolution of the Mikado pheasant remain unclear. Results: We present the draft genome of the Mikado pheasant, which consists of 1.04 Gb of DNA and 15, 972 annotated protein-coding genes. The Mikado pheasant displays expansion and positive selection of genes related to features that contribute to its adaptive evolution, such as energy metabolism, oxygen transport, hemoglobin binding, radiation response, immune response, and DNA repair. To investigate the molecular evolution of the major histocompatibility complex (MHC) across several avian species, 39 putative genes spanning 227 kb on a contiguous region were annotated and manually curated. The MHC loci of the pheasant revealed a high level of synteny, several rapidly evolving genes, and inverse regions compared to the same loci in the chicken. The complete mitochondrial genome was also sequenced, assembled, and compared against four long-tailed pheasants. The results from molecular clock analysis suggest that ancestors of the Mikado pheasant migrated from the north to Taiwan about 3.47 million years ago. Conclusions: This study provides a valuable genomic resource for the Mikado pheasant, insights into its adaptation to high altitude, and the evolutionary history of the genus Syrmaticus, which could potentially be useful for future studies that investigate molecular evolution, genomics, ecology, and immunogenetics.